2023
DOI: 10.4111/icu.20220370
|View full text |Cite
|
Sign up to set email alerts
|

Role of microbiome and its metabolite, short chain fatty acid in prostate cancer

Abstract: The microbiome which is an assembly of all microbes living inside our bodies performs a major role in maintaining human health and wellness. It has been found that the imbalance of the microbiome can cause various diseases in humans. Similarly, there is growing evidence that the microbiome largely affects a person’s chance of contracting certain cancers and how the disease develops and progresses. Studies have shown that about 15% to 20% of all cancers are caused by microbial pathogens. The prevalence of prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…SCFAs are metabolites of the microbiome that have a role in regulating immunity and inhibiting histone deacetylases [ 56 ]. The production of SCFAs in the gut microbiota is influenced by various host, environmental, dietary, and microbial factors [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs are metabolites of the microbiome that have a role in regulating immunity and inhibiting histone deacetylases [ 56 ]. The production of SCFAs in the gut microbiota is influenced by various host, environmental, dietary, and microbial factors [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings imply that SCFAs could be very important in developing PCA. Anaerofilum is protective because it reduces inflammation caused by Alistipes , which produce pro-inflammatory mediators and raise the risk of PCA [ 30 , 36 ].…”
Section: Reviewmentioning
confidence: 99%
“…The gut-microbiota-derived SCFAs contribute to the modulation of HDACs [ 101 ]. In return, this SCFA-mediated HDAC modulation may play a crucial role in cell homeostasis.…”
Section: Microbiome-derived Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%
“…Conversely, research studies have recently reported the association between SCFAs and PCa progression [ 101 ]. For example, Matsushita et al [ 107 ] reported that SCFAs promoted PCa growth through IGF1 signaling in Pten knockout mice [ 107 ].…”
Section: Microbiome-derived Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%
See 1 more Smart Citation